2008
DOI: 10.1007/s10646-008-0197-x
|View full text |Cite
|
Sign up to set email alerts
|

Microalgal photosynthetic activity measurement system for rapid toxicity assessment

Abstract: A systematic biosensor is constructed for the estimation of toxic compounds based on photosynthetic activity measurement in Selenastrum capricornutum cells. The photosynthetic response was evaluated as a function of light intensity, cell concentration and initial dissolved oxygen. The inhibitory effect of some toxicants (1-butyl-3-methylimidazolium tetrafluoroborate, methanol) on dissolved oxygen production was also determined. In all cases, a toxic response was detected (i.e. a dose-related inhibition of phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Additionally, the log 10 EC 50 (/µM) values of methanol, dimethylformamide, and isopropanol estimated using the same alga for 96 h were 5.85, 4.37, and 5.29, respectively (Cho et al 2008a). The log 10 EC 50 value of 1-butyl-3-methylimidazolium tetrafluoroborate measured by the presented system was very similar to that by traditional algal toxicity test for 96 h (Cho et al 2008b). For the practical application of this system, it is necessary to improve its sensitivity by increasing the incubating time of algae with toxicants, using more sensitive photosynthetic organisms to specific toxicants, or using extracted enzymes that play important role in photosynthesis.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Additionally, the log 10 EC 50 (/µM) values of methanol, dimethylformamide, and isopropanol estimated using the same alga for 96 h were 5.85, 4.37, and 5.29, respectively (Cho et al 2008a). The log 10 EC 50 value of 1-butyl-3-methylimidazolium tetrafluoroborate measured by the presented system was very similar to that by traditional algal toxicity test for 96 h (Cho et al 2008b). For the practical application of this system, it is necessary to improve its sensitivity by increasing the incubating time of algae with toxicants, using more sensitive photosynthetic organisms to specific toxicants, or using extracted enzymes that play important role in photosynthesis.…”
Section: Discussionsupporting
confidence: 72%
“…The reason why the initial oxygen level was decreased to 1-3 mg L −1 was to easily observe the change of oxygen concentration and to overcome potential problem of oxygen build-up inside of reaction vessel. However, our previous experiments (Cho et al 2008b) showed that initial oxygen concentration did not significantly affect the photosynthetic activity. The gas mixture used in this experiment contained 99% N 2 and 1% CO 2 so as to supply an extra carbon source for the algal photosynthesis.…”
Section: Microalgal Strain and Culture Conditionsmentioning
confidence: 78%
See 2 more Smart Citations
“…studied the toxicity of a mixture of six organophosphorus pesticides to the luminescent bacterium Q67. All of the mixture toxicities observed were similar to the toxicities predicted by using the concentration addition (CA) model, but the mixture toxicities also correlated well with those predicted by the independent action (IA) model at low concentrations.Toxicity Assays Cho et al (2008a). constructed a systematic biosensor for estimating the toxicity of toxicants based on photosynthetic measurements in Selenastrum capricornutum cells.…”
mentioning
confidence: 99%